A case of diffuse Cutaneous Leishmaniasis in a HIV positive patients - Patwary, Md Ismail; Rahman, Matiur; Ahmed, Saleh (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Not available DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11349 J Bangladesh Coll Phys Surg 2011; 29: 246